The Effect of Giving Gel Combination of Binahong Leaf Extract and Turmeric Rhizome Extract on Histopathological Epithelial Thickness in II B Degree Burn of Rattus norvegicus - Indriyanti, Astrid; Rachmawati, Kadek; Maslachah, Lilik; Damayanti, Ratna; Hidayatik, Nanik; Setiawan, Boedi (Universitas Airlangga, 2023)
This aim of this research was to study the effect of giving a combination gel of binahong (Anredera cordifolia) leaf and turmeric (Curcuma longa Linn) rhizome extract on histopathology of epithelial thickness which has II B degree burns. Twenty five male white rats (Rattus norvegicus) were divided into five groups. K(-) group was normal skin, K(+) group was skin burns treated with 1% silver sulfadiazine, P1, P2, and P3 was skin burns treated with gel combination of binahong leaf extract and turmeric rhizome extract with increase concentration of binahong leaf extract i.e. 1.25%, 2.5%, and 5%, while the concentration of turmeric rhizome extract i.e. 2% for each treatment. The combination gel of binahong leaf extrac 1.25% and turmeric rhizome extract 2% has potential to be an effective treatment for II B burns as indicated by increased of epithelial thickness. Therefore, this study concluded that 1.25% combination gel of binahong leaf extract and turmeric rhizome extract 2% is the effective dosage to increase epithelial thickness on II B healing degree burns wound healing.